Repercussions on sarcomeres of the myotendinous junction and the myofibrillar type adaptations in response to different trainings on vertical ladder - Rocha, Lara Caetano [UNESP] (2020)
The myofibrillary types establish to the skeletal muscle functional and adaptive properties that influence the sarcomeric arrangement during muscle contraction and may have repercussions on an important related force transmission region of the locomotor apparatus, the myotendinous junction (MTJ). This study aimed to describe changes in myofibrillary type and sarcomeric lengths in the belly muscle and MTJ of the soleus and plantaris muscles associated with training protocols in vertical ladder. Thirty adults male Wistar rats were divided into three groups (n = 10): Control (CTR), No-load Training (NLT), and Load Training (LT). Morphoquantitative analysis of different fibers types and sarcomere lengths were performed in distinct regions of plantaris and soleus muscles. In the plantaris muscle with both trainings, there was an increase in the cross-sectional area (CSA) in Type I and II fibers (p <.0001) while sarcomeric lengths revealed greater lengths in the proximal and distal sarcomeres of NLT, although in the LT we found greater lengths in the belly and MTJ sarcomeres. The soleus muscle showed an increase in CSA muscle fiber only in the NLT (p <.0001) and revealed alterations in belly and MTJ sarcomere lengths with training. We concluded that plantaris muscle has an adaptive effect directly associated with training load, with hypertrophy in both trainings and sarcomere length inverse from belly and MTJ, in LT associated with increased force generation and transmission at the MTJ, although soleus muscle has a lower adaptive response to training stimuli with variation in the belly and distal sarcomere of the MTJ.